Repurchase Intention of Bukalapak Customers Viewed From The Quality of E-Service, E-Word of Mouth and E-Satisfaction - Heri Prabowo; Sutrisno; Henry Casandra Gultom; Ratih Pratiwi (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
This research was conducted to determine the factors that influence repurchase intentions for online purchases at Bukalapak. The factors studied included e-service quality with the intervening variables e-word of mouth and e-satisfaction. The research method was carried out using a quantitative approach, with a population of people who had shopped online at Bukalapak. The number of samples collected was 198 respondents. The collected data were then analyzed using Structural Equation Modeling (SEM). Based on the analysis that has been done, it can be concluded that e-service quality has no effect on repurchase intention, e-service quality has an effect on e-word of mouth, e-satisfaction has an effect on –satisfaction. e-word of mouth has an effect on repurchase intention and e-satisfaction has an effect on repurchase intention. To grow repurchase intention from electronic service quality, it needs to be strengthened through electronic word of mouth and e-satisfaction. Keywords: bukalapak customers, e-service quality, e-word of mouth, e-satisfaction, repurchase intention